Fremont [videorecording (DVD)] - Jalali, Babak, 1978-; Jalali, Babak, 1978-; Cavalli, Carolina; Valladao, Laura; Sebastian, Caroline; Schricker, Mahmood; Zada, Anaita Wali; Turkington, Gregg, 1967-; White, Jeremy Allen (Music Box Films, 2023)
Afghan refugee Donya lives in Fremont but works at a fortune cookie factory in San Francisco. Seeking connection, she decides to send a message out to the world one sentence at a time by recording her story on the fortunes.